CT-Derived spleen volume accurately diagnoses severe portal hypertension at HVPG thresholds of 16 mmhg - Xinyu Chen; Jiamei Zhou; Yicheng Lin; Kefeng Jia; Jiajun Tian; Fenghui Li; Rong Lv; Weili Yin; Fang Wang; Ping Zhu; Chao Yang; Jiayin Wang; et al. (Scientific Reports)
Abstract To investigate the diagnostic utility of a noninvasive method based on spleen volume for the accurate diagnosis of severe portal hypertension (PH). We enrolled 260 patients undergoing hepatic venous pressure gradient (HVPG) assessment and enhanced CT at Tianjin Third Central Hospital (December 2019–July 2023), with clinical data collected. Patients were stratified by HVPG levels: ≥16 mmHg (severe PH group) and < 16 mmHg (non-severe PH group). We included 120 cirrhotic patients who met the inclusion criteria. Splenic volume exhibited a linear correlation with HVPG (r = 0.364, p < 0.001). Univariate and multivariate logistic regression analyses identified spleen volume, age, and serum albumin as independent risk factors for severe PH (p < 0.05). Accordingly, a clinical diagnostic model was developed, named the “S-HVPG” score. The area under the curve (AUC) for the “S-HVPG” score was 0.803, with an optimal threshold of 0.694, achieving sensitivity, specificity, positive predictive value(PPV), and negative predictive value (NPV) of 78.8%, 74.3%, 88.2%, and 59.1%, respectively. The spleen volume-based “S-HVPG” scoring system introduces a novel, straightforward, noninvasive approach for diagnosing severe PH. A cutoff value of 0.694 for the S-HVPG score effectively distinguishes patients with severe PH from those with cirrhosis.